Financial Crisis: Time to Manage Earnings? - Bruno Franceschetti (Australasian Accounting, Business and Finance Journal, 2020)
Previous research on how financial crisis affects managers’ earnings management behavior has resulted in different scenarios with inconclusive results. To address the ambiguity in the findings in the literature, the present study presents critical realism as an alternative to the positivist mainstream approach. The study argues against the existence of a causal law based on a constant conjunction model (i.e., whenever a financial crisis happens, earnings management happens) and concludes that financial crisis cannot be seen as the cause of earnings management. Finally, it suggests exploring other structures at work that might be responsible for earnings management.
Keywords: Earnings quality; earnings management; causal law; financial crisis; critical realism; positivism